The Dual Role of Women Farm Laborers on Family Welfare in Tigabinanga Village, Tigabinanga Sub-District, Karo District - Sebayang, Rebekha Prisilia; Harahap, R. Hamdani; Bengkel, Bengkel (PT FORMOSA CENDEKIA GLOBAL, 2024)
Individuals or groups may satisfy their living requirements in a variety of ways. We refer to these techniques as survival tactics. One demographic with a weak economy is the farm laborers in Tigabinanga Village, Tigabinanga District, Karo Regency. Despite their shortcomings or restrictions, women agricultural workers strive to satisfy their fundamental necessities by working to make a livelihood in order to improve the economy. Despite being employed as agricultural laborers, these ladies are nevertheless capable of doing their jobs. In order to support the welfare of families, this research attempts to learn more about the dual function that female agricultural workers play. Literature reviews, observations, interviews, and documentation are the methods utilized to gather data. To draw conclusions, field data are then subjected to qualitative analysis. The study's findings also demonstrate how farm workers fulfill their dual roles by continuing to perform reproductive duties, such as maintaining Human Resources (HR) and performing household chores like cooking, fetching water, searching for firewood, shopping, ensuring family health and nutrition, and raising and educating children. Work that creates items and services for sale and consumption is referred to as productive roles (farmers, fishers, consultants, services, entrepreneurs and entrepreneurship). Political involvement and service projects are related to social roles. Women often do the majority of volunteer community service projects.